2017
DOI: 10.1364/ol.42.002390
|View full text |Cite
|
Sign up to set email alerts
|

Robust real-time 3D single-particle tracking using a dynamically moving laser spot

Abstract: Real-time three-dimensional (3D) single-particle tracking uses optical feedback to lock on to freely diffusing nanoscale fluorescent particles, permitting precise 3D localization and continuous spectroscopic interrogation. Here we describe a new method of real-time 3D single-particle tracking wherein a diffraction-limited laser spot is dynamically swept through the detection volume in three dimensions using a two-dimensional (2D) electro-optic deflector and a tunable acoustic gradient lens. This optimized meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
91
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 58 publications
(91 citation statements)
references
References 24 publications
0
91
0
Order By: Relevance
“…Enhanced retention of eLNPs in vesicular compartments likely leads to a higher total cytosolic mRNA over time. Since endosomal escape is a transient event, we deployed three-dimensional (3D)-Dynamic Photon Localization Tracking (3D-DyPLoT) that is capable of measuring intracellular transport of individual nanoparticles in live cells on a millisecond temporal resolution 46,47 . 3D-DyPLoT is a real-time 3D single-particle tracking method that locks onto moving fluorescence targets and tracks their 3D position with high spatiotemporal precision.…”
Section: T O S T E R O L -A R G I N I N E β -S I T O S T E R O L -Amentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced retention of eLNPs in vesicular compartments likely leads to a higher total cytosolic mRNA over time. Since endosomal escape is a transient event, we deployed three-dimensional (3D)-Dynamic Photon Localization Tracking (3D-DyPLoT) that is capable of measuring intracellular transport of individual nanoparticles in live cells on a millisecond temporal resolution 46,47 . 3D-DyPLoT is a real-time 3D single-particle tracking method that locks onto moving fluorescence targets and tracks their 3D position with high spatiotemporal precision.…”
Section: T O S T E R O L -A R G I N I N E β -S I T O S T E R O L -Amentioning
confidence: 99%
“…High-resolution live-cell imaging. Three-dimensional trajectories of internalized LNPs and eLNPs were collected using 3D-Dynamic Photon Localization Tracking (3D-DyPLoTTo perform 3D-DyPLoT 46,47 , a 640 nm excitation laser (Coherent OBIS,~76 nW at the focus) is focused onto the sample by an objective lens (Zeiss Plan Apo, 100x NA=1.49) and is deflected in a 3D pattern by a 2D electro-optic deflector (ConOptics) and a tunable acoustic gradient (TAG) lens (TAG Optics) 70 . Fluorescence photons from the moving probe are collected by the objective lens and on focused through an emission filter onto a single-photon counting avalanche photodiode (Excelitas SPCM-ARQH-15).…”
Section: Selectionmentioning
confidence: 99%
“…Several approaches can be used to extend this method to three dimensions ( Levi et al, 2005 ; McHale et al, 2007 ). We used the TAG lens resonant axial scanner in combination with galvanometric mirrors to create a cylindrical scan pattern ( Figure 1A ), an approach independently developed for molecular tracking ( Hou et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…3D-SMART. 3D Single-Molecule Active Real-time Tracking (3D-SMART) was achieved by applying these optimized parameters to the previously reported 3D-DyPLoT 25,32 . The general outline is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Feedback is applied using either piezoelectric nanopositioners or galvo mirrors 18 , meaning the target molecule or particle is followed at very high speed, rather than being physically confined. Pioneering work has shown that RT-3D-SPT can lock-on to a wide range of targets, from gold nanoparticles 19, 20 and single quantum dots 21-23 all the way to viruses [24][25][26] , and is easily extended to live cell tracking 27, 28 . This is because the "confinement" is not a physical impediment to the target, but rather a high-speed chase which follows the particle without perturbation.While the pioneering work on RT-3D-SPT by several groups occurred more than a decade ago, the extension of this promising method to real-time 3D single molecule tracking (RT-3D-SMT) has been limited ( Supplementary Table 1).…”
mentioning
confidence: 99%